Honesty: A Multidimensional Study as Motivation for National Character Building - Fitriah M, Suud; Sutrisno; Abd.Madjid (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2020)
Honesty has discussed in various disciplines. Honesty studies have carried out to examine the relationship of honesty with many factors that influence certain fields of science. This study aims to present a multidimensional study to convey the goodness of honesty as a tangible manifestation of the normative message that honesty guide to goodness and it will lead to happiness. This study uses a text analysis method in the form of a literature review through searching several resources. The sources that found is analysed by Wilson's procedure. The results of this study shows that honesty as a whole has a good impact on the physical health and mental health of individuals. Honesty related to many psychological attributes. Therefore, it recommended embedding motivations in educational honesty that concluded from various scientific disciplines.